Unknown cis-[(DMSO)2ClCuII(μ-Cl)2CuIICl(DMSO)2] isomer obtained via new [Cu4Cl8(DMSO)8(hmta)] template complex. Issue 3 (1st February 2017) - Vakulka, Andrii; Goreshnik, Evgeny
Abstract: A missed cis isomeric form of a well-known trans -[CuCl2 (DMSO)2 ]n complex has been prepared via the tetranuclear [Cu4 Cl8 (DMSO)8 (hmta )] complex. Structurally, both complexes were found to be molecular i.e. [Cu4 Cl8 (DMSO)8 (hmta )] consists of isolated tetracoordinated hexamethylenetetramine molecules, whereas the cis -complex consists of isolated [(DMSO)2 ClCu II (μ-Cl)2 Cu II Cl(DMSO)2 ] clusters. It should also be noted that the cis -configuration of DMSO molecules in [(DMSO)2 ClCu II (μ-Cl)2 Cu II Cl(DMSO)2 ] was directly transferred from that of [Cu4 Cl8 (DMSO)8 (hmta )], while the trans -[CuCl2 (DMSO)2 ]n isomer was always formed as a final stable product. Abstract :